Penerapan Metode Waterfall Dalam Perancangan Sistem Informasi Geografis Pemetaan Populasi Ternak Di Kabupaten Malaka Berbasis Web Menggunakan System Block Diagram (Sbd) - Da Silva, Yoseph Ardi Mariano; Nababan, Darsono; Lestari, Anastasia Kadek Dety; Maneno, Regolinda (Journal of Information and Technology, 2024)
Abstract - This research focuses on implementation waterfall method in designing a web-based geographic information system for mapping livestock populations in Malacca Regency using a block diagram (SBD) system. Malacca Regency has dominating livestock potential,This is based on data sourced from (Animal Husbandry Division, Malacca Regency Agricultural Service, 2022), which records the livestock population in 12 sub-districts in Malacca Regency, including 265 horses and 265 cows.71,095 head, 692 buffaloes, as many goats46,337head, 56,078 pigs, 446,072 chickens and 3,299 ducks The aim of this research isto assist Malacca Regency Animal Husbandry Service officers and the community in searching for the location of all livestock spread across Malacca Regency and knowing the percentage data which makes it easier to obtain information.With this information system, it is hoped to make it easier for the public to find the location and number of livestock in Malacca Regency which can be accessed via the website. This research uses the method Waterfall scontains research information in the process of creating the "SIPETER" system. The stages of creating a system using the Waterfall method consist of 5 stages, namely: Requirements Analysis (Analysis of software requirements), System Design (Design), Implementation (Creation of program code), Integration & Testing (Testing), Operation & Maintenance (Support or Maintenance). The test results show that the system successfully fulfills the expected functionality so that makes it easier for the public to find the location and number of livestock in Malacca Regency which can be accessed via the website. Abstrak - Penelitian ini berfokus pada penerapan metode waterfall dalam perancangan sistem informasi geografis pemetaan populasi ternak di kabupaten malaka berbasis web menggunakan system block diagram (sbd). Kabupaten Malaka memiliki potensi peternakan yang mendominasi, Hal itu didasarkan data yang bersumber dari (Bidang Perternakan Dinas Pertanian Kabupaten Malaka, 2022), yang mendata populasi ternak di 12 kecamatan yang ada di Kabupaten Malaka meliputi, kuda sebanyak 265 ekor, sapi sebanyak 71.095 ekor, kerbau sebanyak 692 ekor, kambing sebanyak 46.337 ekor, babi sebanyak 56.078 ekor, ayam sebanyak 446.072 ekor dan itik sebanyak 3.299 ekor. Tujuan penelitian ini adalah untuk membantu petugas Dinas Peternakan Kabupaten Malaka dan masyarakat dalam melakukan pencarian lokasi semua ternak yang tersebar di Kabupaten Malaka dan mengetahui persentase data yang mempermudah mendapatkan informasi. Dengan sistem informasi ini, diharapkan untuk memudahkan masyarakat dalam mencari lokasi dan jumlah ternak yang ada di Kabupaten Malaka yang dapat diakses melalui website. Penelitian ini menggunakan metode Waterfall berisi informasi penelitian dalam proses pembuatan sistem “SIPETER”. Adapun tahapan pembuatan sistem menggunakan metode Waterfall ini terdiri atas 5 tahapan yaitu: Requirement Analysis (Analisis kebutuhan perangkat lunak), System Design (Desain), Implementation (Pembuatan kode program), Integration & Testing (Pengujian), Operation & Maintenance (Pendukung atau Pemeliharaan). Hasil pengujian menunjukkan bahwa sistem berhasil memenuhi fungsionalitas yang diharapkan sehingga memudahkan masyarakat dalam mencari lokasi dan jumlah ternak yang ada di Kabupaten Malaka yang dapat diakses melalui website.